Effect and features of information technology-based interventions on self-management in adolescent and young adult kidney transplant recipients: a systematic review - Ganjali R; Khoshrounejad F; Mazaheri Habibi MR; Taherzadeh Z; Golmakani R; Mostafavi SM; Eslami S (Dove Medical Press, 2019)
Raheleh Ganjali,1 Farnaz Khoshrounejad,1 Mohammad Reza Mazaheri Habibi,2 Zhila Taherzadeh,3 Reza Golmakani,4 Sayyed Mostafa Mostafavi,1 Saeid Eslami1,5,6 1Department of Medical Informatics, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 2Department of Health Information Technology, Varastegan Institute for Medical Sciences, Mashhad, Iran; 3Neurogenic Inflammation Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 4Department of Emergency Medicine, Doctor Shariati Hospital, Mashhad University of Medical Sciences, Mashhad, Iran; 5Pharmaceutical Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 6Department of Medical Informatics, University of Amsterdam, Amsterdam, the NetherlandsCorrespondence: Saeid EslamiDepartment of Medical Informatics, Mashhad University of Medical Sciences, Azadi Street, Mashhad, IranTel +98 513 800 2429Fax +98 513 800 2445Email Eslamis@mums.ac.irIntroduction: Adolescent and young adult periods are characterized by increased risk-taking, impulsive behavior, and nonadherence issues, which makes it equally challenging for patients and their health care professionals. Health information technology (IT) has the potential to empower patients.Objective: Determine the effects and features of IT-based interventions for self-management of adolescents and young adults in kidney transplant recipients.Materials and Methods: A comprehensive survey was done on Medline and Scopus in September 2018. Eligible studies included randomized controlled trials (RCTs) and quasi-experimental studies focused on automated IT-based interventions. Studies contained information about adolescent and young adult kidney transplant recipients aged under 25, all published in English. The articles were combined with each other based on the classification of outcomes, the type of interventions, and their impact. The studies were categorized based on the impact of interventions as positive and statistically significant, with no effect, or a combined effect (both positive significance and without effect).Results: In this review, of a total of 2,242 retrieved articles, collected from Scopus and PubMed databases, 5 studies met the full-text inclusion criteria. Interventions were performed using computerized systems (3 studies), smartphone application/personal digital ass (PDA) (1 study), and multiple components (1 study). These studies evaluated 15 outcomes, including 7 care process and 8 clinical outcomes. In 6 of 15 outcomes (40%), interventions had a statistically significant positive effect.Conclusion: IT-based interventions such as mobile health/personal digital assistant(PDA), computer systems and multi-component have the potential to improve self-management in adolescents and young adult kidney transplant recipients (care process outcomes). It is recommended to conduct complementary research to examine the effect of IT-based self-management interventions on clinical outcomes in kidney transplant recipients.Keywords: adolescent, young adult, information technology, self-management